Prudent lending restored securitization after the mortgage meltdown - Fuchita, Yasuyuki, 1958-; Herring, Richard; Litan, Robert E., 1950- (Nomura Institute of Capital Markets Research ; Brookings Institution Press, 2009)
"Examining growth of complex securitized structures in U.S. and world markets, provides a timeline of key events, proposing explanations for the resulting financial crisis. Offers suggestions on securitization reform, including a solution to insure the mortgage market against default risk. Provides strategies to increase transparency and encourage more prudent lending"--Provided by publisher.